The Influence of Electronic Word of Mouth and Attractiveness Towards Revisit Intention With Visiting Decision as an Intervening Variable (Case Study on Tourists in Makassar City) - Marini Soeid; Nuraeni Kadir; Andi Nur Massepe (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
One of the foreign exchange earning sectors, encouraging economic growth, increasing regional income, empowering the community's economy, and expanding employment opportunities in the tourism sector. Interestingly a tourist attraction does not necessarily indicate tourist satisfaction with the tourist attraction, which can have an impact on interest in return visits. This study aims to determine e-WOM positive and significant influence on visiting decisions, find out the attractiveness of a positive and significant effect on visiting decisions, know e-WOM has a positive and significant effect on the revisit intention, find out the attractiveness of a positive and significant influence on revisit intention, as well as to determine to visit decision has a positive and significant influence on local tourist revisit intention to attractions in the city of Makassar. The population in this study is the number of tourists determined by 400 respondents. Data collection techniques through questionnaires, literature studies and observations, using path analysis techniques (path analysis). The results showed that directly e-WOM have a positive and significant influence on local tourist visiting decision in the city of Makassar. Attractiveness has a positive and significant influence on tourist visiting decisions. e-WOM has a positive and significant influence on tourist revisit intention. Attractiveness has a positive and not significant influence on tourist revisit intention, and directly, visiting decision has a positive and significant influence on local tourists to revisit intention in the city of Makassar.